Pemanfaatan Mesin Pengaduk Semen/ Concerete Mixer Tenaga Surya dalam Meningkatkan Kualitas Produk Batako dan Paving Block pada UMKM “Utama Bangunan” di Kelurahan Lalolang Kecamatan Tanete Rilau Kabupaten Barru - Muhammad, Mukmin; Rachmat, Andi; Fadhilah, Resky Nur (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
This community service program aims to improve the quality of concrete bricks and paving blocks at the “Utama Bangunan” MSME by utilizing a solar-powered concrete mixer. This innovation was designed to address the limitations of electricity supply and reduce operational costs that previously relied on conventional energy sources. The implementation method included solar panel installation, training on machine operation and maintenance, and production process assistance. The results showed improvements in mixture homogeneity, reduced mixing time, and a 35% decrease in defective products. Additionally, operational costs decreased by an average of 20% per month. The implementation of this technology not only enhanced production quality and quantity but also promoted business sustainability through the use of renewable energy. The program’s success serves as a replicable model for similar MSMEs in rural areas with solar energy potential.